IMPLEMENTASI PROGRAM ENGLISH DAY DALAM MENINGKATKAN KOMPETENSI BAHASA INGGRIS SISWA SMPN.5 PERCUTSEITUAN - Galina, Galina (CV. Aksara Global Akademia, 2023)
: English Day is one of the programs implemented by the English Education Study Program through a grant from the Ministry of Research and Technology. The purpose of implementing the English Day program is to increase students' interest in learning English at SMP Negeri 5 Percut Sei Tuan. In accordance with the demands of the learning system in the COVID-19 Pandemic Era, students are required to be able to follow the teaching and learning process using various media and applications to support the teaching and learning process to run well. The low interest in learning English at SMP Negeri 5 Percut Sei Tuan has become a concern for English Language Faculty FKIP students as they implement grant funds from the English Day program practice. The implementation of the English Day program has taken 80 days started from July 5th to October 7th, 2021. The results of the implementation of the English Day program showed that students' abilities improve in English based on the results of the comparison of scores on the pre-test and post-test, namely, increase the ability to communicate in daily activities, their vocabulary, reading ability, and writing ability.